(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Soil salinization, caused by natural and anthropogenic factors, is a pressing environmental issue in Masis Region, which is one of the important regions of irrigated agriculture in Armenia. To prevent this adverse process the groundwater quality in the region has been evaluated for agricultural uses. For this purpose, the water samples were collected from 27 extraction wells and analyzed for major quality parameters following standard test procedures. Other chemical indices, notably sodium adsorption ratio, permeability index and magnesium hazard, were derived from the measured quality parameters. During the studies the areas with good, permissible and unsuitable groundwater quality for irrigation were determined. According to results obtained for irrigation of agricultural lands in Masis Region (especially in its eastern and southern parts), the usage of highly saline groundwater from shallow horizons should be restricted as much as possible, and in Ranchpar Village, where the groundwater even from the high depths has а high salinity, it is required to use an alternative source of irrigation water.